Overcoming diagnostic issues in precision treatment of pancreatic cancer. Issue 3 (4th May 2018) - Löhr, J.-Matthias; Kordes, Maximilian; Rutkowski, Wiktor; Heuchel, Rainer; Gustafsson-Liljefors, Maria; Russom, Aman; Nilsson, Mats
ABSTRACT: Introduction : With high-throughput DNA analysis with next-generation sequencing (NGS), a new area of comprehensive molecular diagnostics is entering clinic. The profile of biomarkers (mutations and other abnormalities) may lay the foundation for precision treatment. Pancreatic ductal adenocarcinoma (PDAC) represents a challenge with its many aberrations spread over all pathways. Furthermore, suitable samples for molecular diagnostics are difficult to obtain, both for tissue-based (biopsy, cytology) and blood-based (cell-free DNA and circulating tumor cells [CTC]) assays. Areas covered : Biomarkers, material, methods, and management of biomarkers for PDAC in precision treatment. Biomarkers refer multiple biomarkers at the same time. Material refers to the different biological sources including blood-based approaches with CTCs. Methods cover the analysis techniques such as NGS and RNA sequencing. Management comprises the handling of NGS and data analysis, as well as the need for clinically applicable, evidence-based recommendations. Expert commentary : Outstanding problems are the procurement of samples suitable for multiplex biomarker analysis such as NGS. This may be overcome by single-cell sequencing. The final challenge, common to all approaches beyond a limited panel of genes, will be the holistic, evidence-based analysis of NGS data for making clinically relevant treatment recommendations. Outcome studies including cost-effectiveness are pivotal prior to reimbursement.